2022
DOI: 10.31083/j.jin2103084
|View full text |Cite
|
Sign up to set email alerts
|

Shunt Over-drainage, Slit Ventricle Syndrome, Programmable Valves and Anti-Siphon Devices. A Narrative Review of a Multifactorial and Intractable Problem

Abstract: The current management strategy of hydrocephalus mainly involves the insertion of a ventriculoperitoneal shunt and is inherently related with a complication widely known as shunt over-drainage. Albeit this is a well-recognized complication, the true incidence and severity of this phenomenon remains undefined and most probably underdiagnosed, necessitating a more comprehensive pathophysiologic and therapeutic consideration. The slit ventricle syndrome is intimately related with the entity of shunt over-drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Innovations in shunt valve technology have promised benefits in reducing SVS, but outcomes data are mixed. The use of programable valves and antisiphoning devices may have a role in modifying the risk of SVS, 5 but these devices cost $3320 each, limiting their global application. 1 Patients with an extensive history of shunt failures, as rates of shunt failure in the first year are 40%, may benefit more from ETV or the MTV approach suggested by the authors.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Innovations in shunt valve technology have promised benefits in reducing SVS, but outcomes data are mixed. The use of programable valves and antisiphoning devices may have a role in modifying the risk of SVS, 5 but these devices cost $3320 each, limiting their global application. 1 Patients with an extensive history of shunt failures, as rates of shunt failure in the first year are 40%, may benefit more from ETV or the MTV approach suggested by the authors.…”
mentioning
confidence: 99%
“…1 Traditional approaches to SVS include endoscopic third ventriculostomy (ETV), change in shunt hardware, and even cranial vault expansion. [2][3][4][5] In this article, "Extra-Axial Third Ventriculostomy for the Treatment of Slit Ventricle Syndrome: 2-Dimensional Operative Video", 6 the authors describe an alternative approach to slit ventricle syndrome, using a minimal-access craniotomy for third ventriculostomy through fenestration of the lamina terminalis from a subfrontal approach. The authors demonstrate the efficacy of their approach in this small series (14 patients) with limited follow-up.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Panagopoulos D et al [24] conducted a narrative literature review focused on an analysis of shunt overdrainage and slit ventricle syndrome. The authors also reported technological advancements aimed in counteracting these treatment side effects.…”
mentioning
confidence: 99%